2018
DOI: 10.3390/ijms19103229
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Evolutionary Selection: The Cardiovascular Protective Function of the Longevity Associated Variant of BPIFB4

Abstract: Evolutionary forces select genetic variants that allow adaptation to environmental stresses. The genomes of centenarian populations could recapitulate the evolutionary adaptation model and reveal the secrets of disease resistance shown by these individuals. Indeed, longevity phenotype is supposed to have a genetic background able to survive or escape to age-related diseases. Among these, cardiovascular diseases (CVDs) are the most lethal and their major risk factor is aging and the associated frailty status. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 81 publications
0
23
0
Order By: Relevance
“…Therefore, frailty reflects the individual’s biological age and life expectancy better than chronological age [3]. Studies in long-living individuals (LLIs), which, in spite of their exceptional biological age, are protected from and cope better with age-related diseases, confirm this concept [4]. Moreover, several genetic factors that are reportedly implicated in the determination of exceptional longevity are also inversely related with frailty disabilities [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, frailty reflects the individual’s biological age and life expectancy better than chronological age [3]. Studies in long-living individuals (LLIs), which, in spite of their exceptional biological age, are protected from and cope better with age-related diseases, confirm this concept [4]. Moreover, several genetic factors that are reportedly implicated in the determination of exceptional longevity are also inversely related with frailty disabilities [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…The liver-specific thyroxine-binding globulin (TBG) promoter was adopted for the AAV assembling. 6 As a confirmation, GFP fluorescence was detected in the liver (online supplementary Figure S4.A-F), but not in the heart (online supplementary Figure S4.G-J), of mice injected with the AAV-GFP vector. Using an antibody that recognises both the murine and human protein, we demonstrated that WT-BPIFB4 and LAV-BPIFB4 gene transfer induced similar increases in BPIFB4 staining in the heart, with specific localisation of the fluorescent signal in cardiomyocytes (P < 0.01 vs. vehicle; Figure 2B).…”
Section: Bpifb4 Gene Therapy In Diabetic Micementioning
confidence: 83%
“…The prevalence of LAV homozygosity is 14% in centenarians and 10% in controls. 6 BPIFB4 is a secreted protein, its levels are increased in serum of long-living individuals, and high BPIFB4 levels classify their health status. 7 Likewise, homozygous LAV carriers have higher circulating BPIFB4 levels and increased phosphorylated endothelial nitric oxide synthase (eNOS) in circulating mononuclear cells.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, centenarians’ children are more likely to reach extreme ages than their peers and show a decreased incidence of age-related pathologies [ 12 ]. Therefore, the world population of centenarians represents a very interesting genomic model and the analysis of the mechanisms that lead to longevity can be a great tool for understanding healthy aging [ 13 ].…”
Section: Centenarians As a Model To Escape Agingmentioning
confidence: 99%
“…Over the years, genetic analysis approaches, in particular GWAS (genome wide association study), have made possible the identification of genetic variants associated with longevity that confer an advantage in terms of survival [ 13 ].…”
Section: Centenarians As a Model To Escape Agingmentioning
confidence: 99%